Factors affecting the amount of effort expended in responding to questions in behavioural choice experiments - Peter Bonsall; Bill Lythgoe (Journal of Choice Modelling, 2009)
A brief review of theoretical and empirical literature on the effort expended in making choices is followed by the description of an experiment in which participants were asked to respond to a series of road charging scenarios. Participants were asked to estimate the charges payable, to indicate their confidence in that estimate, to say how difficult they had found it to understand the scenario, and to indicate whether they would change their behaviour if the charges were introduced. The time they took to answer each question was recorded and background data was collected on their personal characteristics and attitudes as well as on their attitude to decision-making. Analysis of the resulting data shows that the time taken to estimate the charge and decide on a response varied not only with the characteristics of the scenario and with the order of presentation (indicating a learning, or fatigue, effect), but also with personal characteristics (notably age, educational attainment and self-reported decision-making style). The time taken to estimate a charge was significantly (and positively) related to the degree of difficulty reported and, although additional time devoted to making an estimate generally resulted in more accurate estimates, time taken to produce an estimate was, for the simplest scenarios, associated with increased propensity to error. These findings, particularly on the existence of groups with very different levels of motivation to make careful assessment of costs and benefits, and on the factors influencing the time taken to respond to questions, have implications for our understanding of real-world decision-making and for the way that we should collect and categorise choice data and model the decision-making process. The use of simple questions designed to elicit participants' attitudes to decision-making is seen to show great promise in this context.
Keywords: 330; latency; effort; complexity; accuracy; error; need for Cognition; tolerance of ambiguity